COMPARISON OF SURGICAL SITE INFECTIONS IN DIABETIC VERSUS NON-DIABETIC PATIENTS UNDERGOING CLEAN SURGICAL PROCEDURES AT A TERTIARY CARE HOSPITAL - KHAN, MA; KHAN, WY; DIN, MU; FARMAN, MT; FARMAN, J; FAROOQ, A (Biological and Clinical Sciences Research Journal, 2024)
Surgical site infections (SSIs) are a common complication that can significantly impact recovery, particularly in patients with diabetes. Understanding the incidence of SSIs in diabetic versus non-diabetic patients undergoing clean surgical procedures is critical for improving postoperative outcomes. Objective: This study aims to compare the incidence of surgical site infections (SSIs) in diabetic and non-diabetic patients undergoing clean surgical procedures at a tertiary care hospital. Methods: An observational cohort study was conducted with 110 patients, divided into two groups: Group A (diabetic patients) and Group B (non-diabetic patients). All patients underwent clean surgeries, including hernia repair and laparoscopic cholecystectomy. Postoperative complications, including SSIs, wound dehiscence, and seroma formation, were assessed. Statistical analysis was performed to evaluate differences in complication rates between the two groups, with a significance level set at p < 0.05. Results: SSIs were observed in 10.9% of diabetic patients compared to 3.6% in non-diabetic patients, though this difference was not statistically significant (P = 0.14). Wound dehiscence occurred in 3.6% of diabetics versus 1.8% of non-diabetics (P = 0.55), while seroma formation was noted in 1.8% of diabetics, with no cases in the non-diabetic group (P = 0.31). Conclusion: The incidence of surgical site infections was higher in diabetic patients than in non-diabetic patients undergoing clean surgical procedures, though the difference was not statistically significant. Diabetic patients remain at an increased risk of postoperative complications, highlighting the need for enhanced perioperative care to mitigate infection risks.